Polymerase iota (Pol ι) prevents PrimPol-mediated nascent DNA synthesis and chromosome instability - Mansilla, Sabrina Florencia (2023)
Recent studies have described a DNA damage tolerance pathway choice that involves a competition between PrimPol-mediated repriming and fork reversal. Screening different translesion DNA synthesis (TLS) polymerases by the use of tools for their depletion, we identified a unique role of Pol ι in regulating such a pathway choice. Pol ι deficiency unleashes PrimPol-dependent repriming, which accelerates DNA replication in a pathway that is epistatic with ZRANB3 knockdown. In Pol ι–depleted cells, the excess participation of PrimPol in nascent DNA elongation reduces replication stress signals, but thereby also checkpoint activation in S phase, triggering chromosome instability in M phase. This TLS-independent function of Pol ι requires its PCNA-interacting but not its polymerase domain. Our findings unravel an unanticipated role of Pol ι in protecting the genome stability of cells from detrimental changes in DNA replication dynamics caused by PrimPol.